Interactive effects of As, Cd and Zn on their uptake and oxidative stress in As-hyperaccumulator Pteris vittata. (May 2019) - Abid, Rafia; Manzoor, Maria; De Oliveira, Letuzia M.; da Silva, Evandro; Rathinasabapathi, Bala; Rensing, Christopher; Mahmood, Seema; Liu, Xue; Ma, Lena Q.
Abstract: The effects of arsenic (As), cadmium (Cd) and zinc (Zn) on each other's uptake and oxidative stress in As-hyperaccumulator Pteris vittata were investigated . P. vittata plants were exposed to 50 μM As, Cd and/or Zn for 15 d in 0.2-strength Hoagland solution. When applied alone, P. vittata accumulated 185 mg kg −1 As, 164 mg kg −1 Cd and 327 mg kg −1 Zn in the fronds. While Cd and Zn did not impact each other's uptake, As affected Cd and Zn uptake. Whereas As decreased Zn uptake, Zn affected As speciation in P. vittata fronds, with more arsenate (AsV) than arsenite (AsIII) being present. At 50 μM As, 75 μM Zn increased As accumulation in P. vittata fronds by 10 folds to 2363 mg kg −1 compared to 50 μM Zn. Although AsV was the predominant As species in all tissues, Cd enhanced AsIII levels in the fronds but increased AsV in the roots. Co-exposure of Cd + Zn elevated oxidative stress basing on thiobarbituric acid reactive substances, H2 O2 content, Evans blue dye uptake, membrane injury index and reactive oxygen species (ROS) relative to single metal. By lowering Cd and Zn concentrations in P. vittata fronds, As reduced the associated stress comparative to Cd or Zn treatment. The results enhance our understanding of the mechanisms underlying the interactions between As, Cd and Zn in As-hyperaccumulator P. vittata . Graphical abstract: Image 1 Highlights: Interactive effects of As, Cd and/or Zn in uptake and stress by P. vittata was investigated. As reduced Cd and Zn uptake, but Cd and Zn didn't impact As uptake. Cd and Zn did not impact each other's uptake in P. vittata. Zn inhibited AsV reduction to AsIII and increased As uptake by P. vittata. Highest stress was observed in Zn + Cd treatment, lowest in Zn + As treatment. Abstract : Zn increased As uptake by P. vittata and inhibited AsV reduction to AsIII in P. vittata .